RESULTS OF CLINICAL STUDY OF COMPLEX TREATMENT OF GENERALIZED PERIODONTITIS WITH THE USE OF STRONTIUM DRUGS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - A. V. Samoilenko; L. M. Matvyeyenko (Український стоматологічний альманах, 2021)
The most significant periodontal disorders associated with diabetes mellitus are due to changes in bone tissue. It has become necessary for specific osteotropic therapy that can normalize metabolic processes in the alveolar bone. In turn, currently the most promising in terms of improving osteogenic activity are strontium ions. Strontium ranelate is used to treat osteoporosis due to its antiresorptive and osteoanabolic action. However, its effectiveness against alveolar bone has not been sufficiently studied.